1981
DOI: 10.3102/00346543051001101
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Personal Control and Academic Achievement

Abstract: Perceived control of events is one motivational variable that appears to affect children’s academic achievement. In this review the conceptualization and measurement of the control dimension is discussed from three theoretical perspectives: social learning theory, attribution theory, and intrinsic motivation theories. For each of these three perspectives evidence on the relationship between achievement and perceptions of control is summarized, and possible explanations for the relationship are discussed. Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(63 citation statements)
references
References 91 publications
2
57
1
2
Order By: Relevance
“…Through Academic Choice, teachers provide students with opportunities to plan, enact, and reflect on the process and content of academic work they have chosen. Such autonomy promoting classroom structures have been associated with student motivation and achievement (Stipek & Weisz, 1981).…”
Section: Responsive Classroommentioning
confidence: 99%
“…Through Academic Choice, teachers provide students with opportunities to plan, enact, and reflect on the process and content of academic work they have chosen. Such autonomy promoting classroom structures have been associated with student motivation and achievement (Stipek & Weisz, 1981).…”
Section: Responsive Classroommentioning
confidence: 99%
“…Internal locus of control, therefore, acts as a mediating psychosocial resource. It is associated with higher levels of academic achievement (Crandall, Katkovsky, & Crandall, 1965;Stipek & Weisz, 1981), better mental health, and greater resilience in the face of adversity (Howard, Dryden, & Johnson, 1999). In the LSYPE young people are asked to what extent they agree with the statements: 'Even if I do well at school, I will have a hard time getting a good job'; 'People like me don't have much of a chance in life'; and 'How well you get on in this world is mostly a matter of luck'.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Students' sense of control over their academic performance is one of the most important factors to take into consideration when working towards improving academic achievement (Stipek & Weisz, 1981). Coleman, Campbell, Hobson, McPartland, Mood, Weinfeld et al (1966) and Lynch, Hurford, and Cole (2002) reported that locus of control was a significantly better predictor of grades in contrast to standardized achievement test scores.…”
Section: Introductionmentioning
confidence: 99%